2015
DOI: 10.1016/j.mod.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mineralization of the Ts65Dn Down syndrome mouse appendicular skeleton begins during embryonic development in a Dyrk1a-independent manner

Abstract: The relationship between gene dosage imbalance and phenotypes associated with Trisomy 21, including the etiology of abnormal bone phenotypes linked to Down syndrome (DS), is not well understood. The Ts65Dn mouse model for DS exhibits appendicular skeletal defects during adolescence and adulthood but the developmental and genetic origin of these phenotypes remains unclear. It is hypothesized that the postnatal Ts65Dn skeletal phenotype originates during embryonic development and results from an increased Dyrk1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(51 reference statements)
1
17
1
Order By: Relevance
“…This proposition is supported by ultrasound bone measurements at 11–14 weeks of gestation showing short femur lengths in fetuses with trisomy 21 24 . Abnormal bone development in trisomy 21 is thought to originate from genotype–phenotype interaction during embryonic development 5 . The differences between our sample and the WHO norms varied by age, with a large standard deviation score occurring during the first months of life.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This proposition is supported by ultrasound bone measurements at 11–14 weeks of gestation showing short femur lengths in fetuses with trisomy 21 24 . Abnormal bone development in trisomy 21 is thought to originate from genotype–phenotype interaction during embryonic development 5 . The differences between our sample and the WHO norms varied by age, with a large standard deviation score occurring during the first months of life.…”
Section: Discussionsupporting
confidence: 69%
“…Children with DS have different growth patterns compared to children without DS 3, 4. Abnormal bone development is the most common feature and is hypothesized to be regulated by genetic factors 5 . A review showed that stature of children with DS was 0.4–4.0 standard deviations below that of children without DS 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the change in ultimate stress with treatment, all mechanical changes were in whole bone properties which suggest that it was mostly changes in bone size/geometry that drove mechanical deficits as compared to inferior tissue quality. Similar skeletal deficits including decreases in ultimate force and stiffness were quantified in femurs from euploid mice with only one copy of Dyrk1a [63]. …”
Section: Discussionmentioning
confidence: 83%
“…In contrast, our previous study using a three week administration of EGCG (~10mg/kg/day) showed improved skeletal deficits including femoral bone mineral density, percent trabecular bone volume, trabecular number and trabecular thickness in Ts65Dn mice [63]. These results suggest that in bone, there may be an “inverted U” function of optimal Dyrk1a activity, such that an optimal range of activity is necessary to achieve maximum skeletal strength, and falling below the threshold (as with high doses of EGCG) or exceeding an upper boundary (as with excess activity in trisomy) may be detrimental to bone strength.…”
Section: Discussionmentioning
confidence: 87%
“…This summary is not exhaustive and many additional DS features have been explored using mouse models, such as the mineralisation of long bones ( Blazek et al, 2015 ), the risk of chronic otitis media ( Bhutta et al, 2013 ), and the higher risk of developing myeloproliferative disorders and cancer ( Ng et al, 2015 ; Sussan et al, 2008 ; Malinge et al, 2012 ; Alford et al, 2010 ; Yang et al, 2016 ). Each mouse strain has the potential to provide unique information, and a range of animals, aneuploid and partially trisomic, are important to pinpoint specific candidate genes and dissect the underlying molecular mechanisms.…”
Section: Assessing the Genotype-phenotype Relationship In Dsmentioning
confidence: 99%